Invisible by law: Germany’s immigration policy and the exclusion of undocumented women in Leipzig - Escobar Cuero, Gina Paola (Frontiers in Human Dynamics, 2025)
The intersection of gender, irregular legal status, and economic precarity places undocumented women in Leipzig at heightened risk of exclusion from both healthcare and the labor market. German migration policy, increasingly centered on border enforcement and deterrence, continues to neglect the realities of women working in informal care and domestic sectors. This policy orientation reinforces institutional barriers, especially in reproductive and mental healthcare, and marginalizes undocumented women within systems of care and employment. Between March and June 2025, a structured mini-review of academic and grey literature was conducted using the Vienna University Library and key NGO reports. The review analyzed gendered exclusions across Germany’s legal, healthcare, and labor frameworks, with a particular focus on Leipzig. Findings indicate a striking absence of gender-disaggregated municipal data, perpetuating the invisibility of undocumented women. This invisibility is unintentionally reinforced by Section 87 of the Residence Act (AufenthG), which obliges public authorities to report undocumented individuals, thereby deterring women from accessing healthcare or labor rights protections. The review confirms national trends of labor exploitation and healthcare avoidance among undocumented migrants while highlighting the significant data gaps in Leipzig, which undermine effective local governance. Addressing this invisibility requires gender-sensitive data collection, robust legal firewalls decoupling essential services from immigration enforcement, and targeted municipal investment in safe-reporting mechanisms. Taken together, the Leipzig case demonstrates how migration law, though not explicitly intended for this purpose, produces exclusionary effects and underscores the urgent need for rights-based reforms that recognize undocumented women as social and political actors rather than individuals rendered invisible through policy design and implementation.